Markfuktighetens påverkan på granens tillväxt i Guvarp - Persson,Ylva (Lunds universitets Naturgeografiska institution - Seminarieuppsatser, 2010)
Norway spruce is a coniferous tree with many different fields of application. For an example, they are used as Christmas trees, decoration and as timber or pulpwood. The reason why many foresters in Sweden tend to choose spruce as their main species for plantation is partly because of their fast growth rate and partly because the main products are derived from the actual tree trunks. In the forest of Guvarp, about 7 kilometres south of Perstorp in Skåne, plantation of spruce begun in the middle of 1940. Before this shift in land use, the area was used for agriculture, either for plantation of crops or as pastures. Until recently, the plantation of Guvarp oriented towards Christmas tree production. The trees were planted with a distance of about 1 meter between the seedlings, which is closer than standard for plantation. The remainder of the trees, used for pulpwood, will be growing more closely together. This lowers the production rate and the monetary value of the forest. Soil moisture affects the forest growth of Guvarp particularly because of its usually high content in the soil. A high soil water content have the effect that pores within the soil are filled with water and may drown roots and decomposers in the ground. As a measure to prevent this, the foresters made trenches around the areas that were affected. They also tilled some of their land, using mounding for their plantation. By studying measurements made in this area, it is confirmed that the mounds have a lower soil moisture content than the holes in between. It also shows that the actual moisture content is relatively low, with values between 15-30 % depending on the area. This is due to a lower than normal precipitation amount and a temperature up to 1,5 °C warmer than usual during the measurements done in April. A low soil moisture may stress the plantations of Norway spruce, with effects like drying of the roots, less photosynthesis and a lower nitrification from mycorrhizae, which is a symbiosis between roots and fungus. The results from an inventory that was made for 2 habitats in the area, which both have trees planted in mounds and trees planted without any tilling, shows that the trees on the mounds were shorter, but had wider trunks and trees without tilling were taller with thinner trunks. When the seedlings where planted, the distance between each plant where of equal length, which out rule any differences at the beginning of their growth. The conclusion when it comes to the choice of tilling is that mounding was the right choice for the forest of Guvarp. However, there is one practice that is called inversion which is more effective than mounding, but due to the high cost and difficulty to till correctly, it is discarded from the area.
Keywords: naturgeografi; geografi; markfuktighet; gran; tillväxt; Guvarp; Skåne